O comportamento de consumo e a consciência ambiental do consumidor no contexto beauty care - Silva, Vanessa Almeida da (2017)
This study develops the theme on consumer behavior focused on environmental awareness of products related to health and beauty care, denominated in this study of beauty care, as they have grown the number of individuals who consider environmental issues and seek ecofriendly products. The insertion of the construct that measures environmental awareness is due to the findings based on the perception of consumers about the impact of their purchasing behaviors, strongly associated with environmental problems, the use of sustainable practices by the organizations in their processes, the concern with the environment and the dissemination of the concept of sustainability. At present, it is significant to present a survey with data collection about consumers and their consumption habits, considering their attitudes and beliefs about the acquisition, resistance or even rejection of some products, needing to ponder the attributes that can influence the behavior purchasing decision and consumption decision. The purpose of this study is to develop and test a theoretical model that relates attitudes, subjective norms, control of perceived behavior and an environmental conscience, with an intention and behavior of consumption of personal hygiene products, perfumery and cosmetics corresponding to the context of beauty care. Topics related to marketing and its interconnection with sustainability and innovation, consumer behavior, Planned Behavior Theory (TPB) and environmental awareness were reviewed. A descriptive research was carried out, of qualitative and quantitative nature in different phases. A survey was applied as a procedure for data collection, to a sample of 787 valid questionnaires, analyzed through statistical procedures, such as descriptive statistics, univariate analysis and multivariate data analysis, which was used the modeling technique of Structural Equations (SEE) to test the validity of the relations formulated between the constructs of the model. In the main findings of the study, it was verified that the constructs of the Theory of Planned Behavior did not present significant relations to the point of extracting pertinent result to comprehend the phenomenon. The second order control, referring to environmental awareness, pumping intention and intention of behavior, through the level of significance and positive impact on intention and no behavior of purchase of products from the context of beauty care.